Genome-Wide Identification and Bioinformatics Characterization of Superoxide Dismutases in the Desiccation-Tolerant Cyanobacterium Chroococcidiopsis sp. CCMEE 029 - Napoli, Alessandro; Iacovelli, Federico; Fagliarone, Claudia; Pascarella, Gianmarco; Falconi, Mattia; Billi, Daniela (Frontiers in Microbiology, 2021)
A genome-wide investigation of the anhydrobiotic cyanobacterium Chroococcidiopsis sp. CCMEE 029 identified three genes coding SODs annotated as MnSODs (SodA2.1 and SodA2.2) and Cu/ZnSOD (SodC) as suggested by the presence of metal-binding motifs and conserved sequences. Structural bioinformatics analysis of the retrieved sequences yielded modeled MnSODs and Cu/ZnSOD structures that were fully compatible with their functional role. A signal-peptide bioinformatics prediction identified a Tat signal peptide at the N-terminus of the SodA2.1 that highlighted its transport across the thylakoid/cytoplasmic membranes and release in the periplasm/thylakoid lumen. Homologues of the Tat transport system were identified in Chroococcidiopsis sp. CCMEE 029, and the molecular docking simulation confirmed the interaction between the signal peptide of the SodA2.1 and the modeled TatC receptor, thus supporting the SodA2.1 translocation across the thylakoid/cytoplasmic membranes. No signal peptide was predicted for the MnSOD (SodA2.2) and Cu/ZnSOD, thus suggesting their occurrence as cytoplasmic proteins. No FeSOD homologues were identified in Chroococcidiopsis sp. CCMEE 029, a feature that might contribute to its desiccation tolerance since iron produces hydroxyl radical via the Fenton reaction. The overall-overexpression in response to desiccation of the three identified SOD-coding genes highlighted the role of SODs in the antioxidant enzymatic defence of this anhydrobiotic cyanobacterium. The periplasmic MnSOD protected the cell envelope against oxidative damage, the MnSOD localized in the thylakoid lumen scavengered superoxide anion radical produced during the photosynthesis, while the cytoplasmic MnSOD and Cu/ZnSOD reinforced the defence against reactive oxygen species generated at the onset of desiccation. Results contribute to decipher the desiccation-tolerance mechanisms of this cyanobacterium and allow the investigation of its oxidative stress response during future space experiments in low Earth orbit and beyond.